(r)HDL in theranostics: how do we apply HDL's biology for precision medicine in atherosclerosis management?. (19th March 2021) - B. Uribe, Kepa; Benito-Vicente, Asier; Martin, Cesar; Blanco-Vaca, Francisco; Rotllan, Noemi
Abstract : (r)HDL therapeutics has progressed a long way but has yet to produce fruitful results. Based on what has been learned and on the most innovative perspectives, a new generation of "smart" rHDL is emerging as an alternative for the management of CVD. Abstract : High-density lipoproteins (HDL) are key players in cholesterol metabolism homeostasis since they are responsible for transporting excess cholesterol from peripheral tissues to the liver. Imbalance in this process, due to either excessive accumulation or impaired clearance, results in net cholesterol accumulation and increases the risk of cardiovascular disease (CVD). Therefore, significant effort has been focused on the development of therapeutic tools capable of either directly or indirectly enhancing HDL-guided reverse cholesterol transport (RCT). More recently, in light of the emergence of precision nanomedicine, there has been renewed research interest in attempting to take advantage of the development of advanced recombinant HDL (rHDL) for both therapeutic and diagnostic purposes. In this review, we provide an update on the different approaches that have been developed using rHDL, focusing on the rHDL production methodology and rHDL applications in theranostics. We also compile a series of examples highlighting potential future perspectives in the field.